Season, Transport Duration and Trailer Compartment Effects on Blood Stress Indicators in Pigs: Relationship to Environmental, Behavioral and Other Physiological Factors, and Pork Quality Traits - Sommavilla, Roberta; Faucitano, Luigi; Gonyou, Harold; Seddon, Yolande; Bergeron, Renée; Widowski, Tina; Crowe, Trever; Connor, Laurie; Scheeren, Marina Bergoli; Goumon, Sébastien; Brown, Jennifer (Animals, 2017)
The objective of this study was to assess the effects of the season, travel duration and trailer compartment location on blood creatine-kinase (CK), lactate and cortisol concentrations in 384 pigs and assess their relationships with trailer temperature, heart rate and gastrointestinal tract temperature (GTT), behavior, carcass damage scores and meat quality. Blood CK was greater in pigs transported in summer (p = 0.02), after 18 h transportation (p < 0.001) and in pigs located in C4, C5 and C10 (p = 0.002). In winter, the concentration of blood lactate was higher (p = 0.04) in pigs transported for 6 h in C5. Pigs located in C10 showed higher (p = 0.01) concentration of cortisol than those transported for 18h in C4 in summer. The highest correlations were between blood cortisol and GTT (r = 0.53; p < 0.001), and between blood CK and GTT (r = 0.41; p < 0.001), truck temperature (r = 0.42; p < 0.001), and pHu in the longissimus muscle (r = 0.41; p < 0.001). In conclusion, although increased blood cortisol and CK levels appear to indicate a physical stress condition in transported pigs, the weak to moderate correlations with environmental and other animal welfare indicators suggest that blood stress parameters can only be used as a complementary measurement in the assessment of the pigs' response to transport stress.
Keywords: body temperature; heart rate; behavior; stress response; blood parameters; pigs; transport time; meat quality; season